Hierarchy of Influence on the Implementation of Search Engine Optimization in the Tribun-Bali.com Newsroom - Anggara, Oktava; Gelgel, Ni Made Ras Amanda; Purnawan, Ni Luh Ramaswati (UI Scholars Hub, 2024)
Technological disruption has driven changes in the media and journalism industry, affecting the workflow in the newsroom. One emerging practice in the newsroom is the application of search engine optimization (SEO). This practice raises concerns about editorial decisions being directed toward topics that are